Perform the indicated operation: (x^3+x^2+x/x-2x^2) / (x^3-1/1-3x+2x^2)Show step by step solution to explain the answer

1 Answer | Add Yours

thilina-g's profile pic

thilina-g | College Teacher | (Level 1) Educator

Posted on


We can simplify this by separating it into factors.

`= ((x(x^2+x+1))/(x(1-2x)))/(((x-1)(x^2+x+1))/((1-2x)(1-x)))`

Therefore this simplifies into,

`= -(x^2+x+1)/(1-2x) xx (1-2x)/(x^2+x+1)`

 = -1



`((x^3+x^2+x)/(x-2x^2))/((x^3-1)/(1-3x+2x^2)) = -1`


We’ve answered 317,411 questions. We can answer yours, too.

Ask a question